Method for manufacturing resin member
The method addresses the challenges of resin member manufacturing by using a coating agent with silsesquioxane and (meth)acrylate components, achieving a coating film with improved adhesion and scratch resistance, and simplifying the process to produce resin members with enhanced durability and ease of production.
Patent Information
- Application Number
- JP2023181232
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-05-02
AI Technical Summary
Conventional methods for manufacturing resin members with coating films face challenges such as requiring large storage spaces due to shaped substrates, difficulty in forming uniform coatings, insufficient toughness of two-layer films leading to cracking, and complex and costly processes.
A method involving applying a coating agent with silsesquioxane and (meth)acrylate components to a thermoplastic resin substrate, followed by ultraviolet irradiation to generate bases and radicals for simultaneous sol-gel and radical polymerization, forming a coating film with improved adhesion and scratch resistance, and then heating and pressing the laminate to achieve the desired shape without cracking.
The method enables the formation of a coating film with excellent adhesion to the substrate and high resistance to scratches, while simplifying the manufacturing process and preventing cracks during substrate deformation, thus producing a resin member with enhanced durability and ease of production.
Smart Images

Figure 2025070723000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a resin member. [Background technology]
[0002] Traditionally, inorganic materials such as steel, aluminum, and glass have been used for the components that make up vehicles such as automobiles and trains. In recent years, in order to reduce the weight of vehicles, there has been a trend to replace inorganic parts with organic parts such as plastics. However, while organic materials are lighter than inorganic materials, they are softer and more easily scratched.
[0003] Therefore, in order to improve the durability of parts made of organic materials against scratches, a technique for forming a hard coating on the surface of the part has been proposed. For example, Patent Document 1 describes a coated member having a resin base material, a primer layer formed on the surface of the resin base material, and a hard coat layer formed on the primer layer. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2006-240294 A Summary of the Invention [Problem to be solved by the invention]
[0005] Conventionally, in producing a coated member, a film is formed after a flat resin substrate is molded into a desired shape. However, if the resin substrate is molded into a desired shape before the film is formed, a relatively large space is required for storing the resin substrate. In addition, depending on the shape of the resin substrate, it may be difficult to uniformly form a film on the resin substrate. In order to solve these problems, it is desirable to form a film on the resin substrate before forming the resin substrate into a desired shape.
[0006] However, a coating having a two-layer structure as described in Patent Document 1 has insufficient toughness, and therefore when a coating is formed on a resin substrate and then the resin substrate is molded, there is a problem in that the coating cannot fully conform to the deformation of the resin substrate, resulting in the generation of cracks.
[0007] In addition, when forming a two-layer coating on a resin substrate, it is necessary to sequentially carry out a step of applying a primer onto the resin substrate, a step of drying the primer to form a primer layer, a step of applying a coating agent onto the primer layer, and a step of curing the coating agent to form a hard coat layer, which makes the coating formation process complicated and increases the cost required for the coating formation process.
[0008] The present invention has been made in consideration of the above background, and aims to provide a method for manufacturing a resin member that can form a coating film that has excellent adhesion to a substrate and excellent resistance to scratches through simple operations, and that can suppress the occurrence of cracks in the coating film when the substrate is deformed by pressing. [Means for solving the problem]
[0009] In one aspect of the present invention, a coating agent is applied onto a substrate made of a thermoplastic resin, the coating agent including a film-forming component including a silsesquioxane having a Ta structural unit represented by the following composition formula (1) and a Tc structural unit represented by the following composition formula (2) and a (meth)acrylate (excluding the silsesquioxane), and a film-curing component configured to generate a base and a radical when irradiated with ultraviolet light, Thereafter, the coating agent is irradiated with ultraviolet light to form a coating film made of a cured product of the coating agent on the substrate; Thereafter, the laminate of the substrate and the coating film is heated and pressed to obtain a resin member having a desired shape. (R 1 SiO 3 / 2 ) ···(1) (R 2 SiO 3 / 2 ) ···(2)
[0010] However, R in the composition formula (1) 1 is an acryloyl group or a methacryloyl group, and R in the composition formula (2) 2 is a monovalent hydrocarbon group. Effect of the Invention
[0011] In the method for producing a resin member, a coating agent containing the specific silsesquioxane and (meth)acrylate is applied onto a substrate, and then ultraviolet light is irradiated. When the coating agent is irradiated with ultraviolet light, a base and radicals are generated from the film-curing component. The base generated from the film-curing component can condense the silsesquioxane through a sol-gel reaction. In addition, the radicals generated from the film-curing component can polymerize the (meth)acrylate and the silsesquioxane through radical polymerization.
[0012] Therefore, by irradiating the coating agent with ultraviolet light, the sol-gel reaction and the radical polymerization can proceed in parallel, resulting in segregation of inorganic components derived from silsesquioxane on the surface of the coating film, improving the durability against scratches, and segregation of organic components in the coating film near the substrate, improving adhesion to the substrate.
[0013] In addition, since the coating film has a relatively high toughness, when a laminate of the substrate and the coating film is pressed, the coating film easily deforms following the deformation of the substrate. As a result, it is possible to obtain a resin part having a desired shape while suppressing the occurrence of cracks in the coating film. Furthermore, by heating the coating film, it is possible to further improve the durability of the coating film against scratches.
[0014] As a result, according to the above-mentioned aspect, it is possible to provide a method for manufacturing a resin member that can form a coating film having excellent adhesion to a substrate and excellent resistance to scratches by a simple operation, and that can suppress the occurrence of cracks in the coating film when the substrate is deformed by pressing. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a perspective view of a resin member obtained by a manufacturing method according to an embodiment. [Diagram 2] FIG. 2 is a perspective view of a laminate used in the manufacturing method of the embodiment. [Diagram 3] FIG. 3 is a schematic diagram of a step of pressing a laminate in the manufacturing method of the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] (Coating agent) The coating agent used in the preparation of the resin member includes a film-forming component that forms a coating film by curing, and a film-hardening component for hardening the film-forming component. The composition of each component contained in the coating agent will be described below.
[0017] [Film forming component] The film-forming components include a silsesquioxane and a (meth)acrylate.
[0018] Silsesquioxane The silsesquioxane contained in the film-forming component has a Ta structural unit represented by the following composition formula (1) and a Tc structural unit represented by the following composition formula (2). (R 1 SiO 3 / 2 ) ···(1) (R 2 SiO 3 / 2 ) ···(2)
[0019] However, R in the composition formula (1) 1is an acryloyl group or a methacryloyl group, and R in the composition formula (2) 2 R in the composition formula (2) is a monovalent hydrocarbon group. 2 More specifically, R may be a methyl group, an ethyl group, a propyl group, an isopropyl group, an n-butyl group, an isobutyl group, etc. From the viewpoint of more reliably obtaining the above-mentioned effects, R 2 is preferably a monovalent saturated hydrocarbon group, more preferably a saturated hydrocarbon group having 18 or less carbon atoms, further preferably a methyl group or an ethyl group, and particularly preferably a methyl group.
[0020] A hydroxyl group (-OH) or an alkoxy group (-OR) is bonded to a part of the Si atom in the silsesquioxane. Therefore, the silsesquioxane can be condensed by a base generated from the film hardening component to form an inorganic component in the coating film. In addition, the (meth)acryloyl group in the silsesquioxane can be polymerized together with the (meth)acryloyl group in the (meth)acrylate by a radical generated from the film hardening component.
[0021] The molar ratio of the content of the Ta structural unit to the total content of the Ta structural unit and the Tc structural unit in the silsesquioxane may be, for example, more than 0 mol% and 60 mol% or less. The weight average molecular weight of the silsesquioxane may be 2,000 or more. By setting the content of the Ta structural unit in the silsesquioxane within the specific range and setting the weight average molecular weight of the silsesquioxane within the specific range, inorganic components derived from the silsesquioxane can be segregated on the surface of the coating film after curing. As a result, a surface layer mainly composed of inorganic components can be formed on the surface of the coating film, and an inner layer mainly composed of organic components can be formed between the surface layer and the substrate. Such a coating film having a two-layer structure has excellent adhesion to a substrate made of resin and durability against scratches.
[0022] The content of Ta structural unit in silsesquioxane is preferably 5 mol% or more, more preferably 10 mol% or more, even more preferably 15 mol% or more, particularly preferably 20 mol% or more, and most preferably 25 mol% or more, based on the total content of Ta structural unit and Tc structural unit. In this case, the wear resistance of the coating film can be further improved.
[0023] When forming the preferred range of the content of the Ta structural unit in the silsesquioxane, the upper limit and the lower limit of the content of the Ta structural unit described above can be combined arbitrarily.For example, the preferred range of the content of the Ta structural unit in the silsesquioxane may be 5 mol% or more and 60 mol% or less, 10 mol% or more and 60 mol% or less, 15 mol% or more and 60 mol% or less, 20 mol% or more and 60 mol% or less, or 25 mol% or more and 60 mol% or less, based on the total content of the Ta structural unit and the Tc structural unit.
[0024] The weight average molecular weight of the silsesquioxane is preferably 2,500 or more, more preferably 3,000 or more, even more preferably 3,500 or more, and particularly preferably 4,000 or more. In this case, the coating film having the above-mentioned two-layer structure can be more easily formed, and the adhesion between the coating film and the substrate and the durability against scratches can be improved.
[0025] On the other hand, if the weight-average molecular weight of the silsesquioxane is too large, the viscosity of the coating agent will increase too much, which may lead to deterioration of the workability in applying the coating agent. In order to avoid such problems, the weight-average molecular weight of the silsesquioxane is preferably 25,000 or less, more preferably 20,000 or less, even more preferably 15,000 or less, and particularly preferably 13,000 or less.
[0026] When forming the preferred range of the weight-average molecular weight of silsesquioxane, the upper limit and the lower limit of the weight-average molecular weight of silsesquioxane described above can be combined arbitrarily.For example, the preferred range of the weight-average molecular weight of silsesquioxane may be 2,000 or more and 25,000 or less, 2,000 or more and 20,000 or less, 2,500 or more and 15,000 or less, 3,000 or more and 15,000 or less, 4,000 or more and 15,000 or less, or 4,000 or more and 13,000 or less.
[0027] The silsesquioxane may further contain a Q structural unit represented by the following composition formula (3): In this case, the molar ratio of the content of the Q structural unit to the total content of the Ta structural unit, the Tc structural unit, and the Q structural unit in the silsesquioxane is preferably more than 0 mol% and 25 mol% or less. (SiO 4 / 2 ) ···(3)
[0028] By introducing Q structural unit into silsesquioxane, the abrasion resistance of coating film can be further improved.From the viewpoint of improving the abrasion resistance of coating film, the content of Q structural unit in silsesquioxane is preferably 1 mol% or more, more preferably 2 mol% or more, and even more preferably 3 mol% or more, based on the total of the content of Ta structural unit, the content of Tc structural unit and the content of Q structural unit.
[0029] On the other hand, if the content of the Q structural unit in the silsesquioxane is excessively large, silsesquioxane aggregates are likely to occur in the coating film, which may lead to deterioration of the appearance of the coating film and deterioration of the abrasion resistance, etc. These problems can be easily avoided by setting the content of the Q structural unit in the silsesquioxane to preferably 25 mol % or less, more preferably 20 mol % or less, even more preferably 15 mol % or less, particularly preferably 10 mol % or less, and most preferably 8 mol % or less, based on the total content of the Ta structural unit, the Tc structural unit, and the Q structural unit.
[0030] When forming the preferred range of the content of the Q structural unit in the silsesquioxane, the upper limit and the lower limit of the content of the Q structural unit described above can be combined arbitrarily.For example, the preferred range of the content of the Q structural unit in the silsesquioxane may be 1 mol% or more and 20 mol% or less, 1 mol% or more and 15 mol% or less, 2 mol% or more and 10 mol% or less, 2 mol% or more and 8 mol% or less, or 3 mol% or more and 8 mol% or less, based on the total of the content of the Ta structural unit, the content of the Tc structural unit, and the content of the Q structural unit.
[0031] The content of silsesquioxane in the coating agent is preferably 30 parts by mass or more and 150 parts by mass or less, more preferably 40 parts by mass or more and 125 parts by mass or less, and even more preferably 50 parts by mass or more and 100 parts by mass or less, relative to 100 parts by mass of (meth)acrylate. In this case, the effect of improving hardness by the inorganic component and the effects of improving adhesion and flexibility by the organic component can be obtained in a better balance.
[0032] The silsesquioxane used in the coating agent can be obtained, for example, by condensing a plurality of alkoxysilanes including a (meth)acryloxyalkyltrialkoxysilane which becomes a Ta structural unit and an alkyltrialkoxysilane which becomes a Tc structural unit.
[0033] Examples of (meth)acryloxyalkyltrialkoxysilanes that are Ta structural units include 3-acryloxypropyltrimethoxysilane, 3-acryloxypropyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, and 3-methacryloxypropyltriethoxysilane. These (meth)acryloxyalkyltrialkoxysilanes may be used alone to synthesize silsesquioxanes. In addition, two or more (meth)acryloxyalkyltrialkoxysilanes may be used in combination to synthesize silsesquioxanes.
[0034] As the alkyltrialkoxysilane that is the Tc structural unit, for example, methyltrimethoxysilane, ethyltrimethoxysilane, propyltrimethoxysilane, isopropyltrimethoxysilane, n-butyltrimethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, propyltriethoxysilane, isopropyltriethoxysilane, n-butyltriethoxysilane, etc. can be used. These alkyltrialkoxysilanes may be used alone to synthesize silsesquioxane. In addition, two or more kinds of alkyltrialkoxysilanes can be used in combination to synthesize silsesquioxane.
[0035] When introducing a Q structural unit into silsesquioxane, tetraalkoxysilane may be used to synthesize the silsesquioxane in addition to the above-mentioned trialkoxysilane. As the tetraalkoxysilane that becomes the Q structural unit, for example, tetramethoxysilane, tetraethoxysilane, etc. may be used. These tetraalkoxysilanes may be used alone to synthesize the silsesquioxane. In addition, two or more kinds of tetraalkoxysilanes may be used in combination to synthesize the silsesquioxane.
[0036] The reaction conditions for synthesizing silsesquioxane using alkoxysilane are not particularly limited, and alkoxysilane may be condensed by a known method.
[0037] (Meth)acrylates In this specification, (meth)acrylate refers to acrylic acid ester and methacrylic acid ester. However, the above-mentioned silsesquioxane is excluded from (meth)acrylate. The (meth)acrylate contained in the film-forming component can be radically polymerized by the radical generated from the film-curing component to form an organic component in the coating film. In addition, the (meth)acrylate can react with the (meth)acryloyl group contained in the silsesquioxane and bond to the silsesquioxane.
[0038] By blending (meth)acrylate in the coating agent, an inner layer mainly composed of an organic component can be formed in the coating film. By forming an inner layer mainly composed of an organic component in the coating film in this way, the toughness of the coating film can be improved and the adhesion between the substrate and the coating film can be further improved. As a result, when a laminate of the substrate and the coating film is pressed, the coating film becomes more likely to deform in accordance with the substrate, and the occurrence of cracks can be suppressed.
[0039] The film-forming component may contain one type of (meth)acrylate selected from the group consisting of acrylates and methacrylates, or may contain two or more types of (meth)acrylates. Examples of the (meth)acrylate contained in the film-forming component include (meth)acrylic acid monoesters such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, 1-methylethyl (meth)acrylate, butyl (meth)acrylate, 2-methylpropyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 2-(allyloxymethyl)methyl acrylate; (meth)acrylic acid diesters such as 1,6-hexanediol di(meth)acrylate, polyethylene glycol di(meth)acrylate, and isocyanuric acid ethylene oxide-modified di(meth)acrylate; and (meth)acrylic acid esters having three or more (meth)acryloyl groups such as trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, and isocyanuric acid ethylene oxide-modified tri(meth)acrylate. The (meth)acrylate may be a monomer of the above-mentioned compound, or may be an oligomer in which a plurality of monomers are polymerized in advance.
[0040] The (meth)acrylate preferably has three or more (meth)acryloyl groups per molecule. In this case, the structural unit derived from the (meth)acrylate and the structural unit derived from the silsesquioxane can be polymerized in a network shape. As a result, the hardness of the coating film can be increased, and the durability against scratches can be improved. In addition, from the viewpoint of further improving weather resistance, the (meth)acrylate preferably has an isocyanuric ring.
[0041] [Film curing component] The coating agent contains a film-curing component for promoting the curing reaction of the film-forming component. The film-curing component is configured to generate both a base and a radical when irradiated with ultraviolet light. For example, the film-curing component may contain a photobase generator configured to generate both a base and a radical when irradiated with ultraviolet light. In addition, the film-curing component may contain both a photobase generator configured to generate a base when irradiated with ultraviolet light, and a photoradical polymerization initiator configured to generate radicals when irradiated with ultraviolet light.
[0042] Photobase generator The photobase generator may be configured to generate at least a base when irradiated with ultraviolet light. That is, the photobase generator may be a compound that generates only a base when irradiated with ultraviolet light. The photobase generator may also be a compound that generates both a base and a radical when irradiated with ultraviolet light.
[0043] More specifically, as the photobase generator, a compound can be used that has an ultraviolet light absorbing portion that contains an aromatic ring such as a benzene ring, a naphthalene ring, a phenanthrene ring, an anthracene ring, an anthraquinone ring, a xanthene ring, or a thioxanthene ring in its molecular structure and absorbs ultraviolet light, and a base portion bonded to the ultraviolet light absorbing portion and that contains a structural unit that becomes a base when detached from the ultraviolet light absorbing portion, such as a primary to tertiary amino group, a quaternary ammonium cation, a carbamoyl group, a carbamate bond, an imino bond, or a nitrogen-containing heterocycle.
[0044] Examples of such compounds include 1,2-dicyclohexyl-4,4,5,5-tetramethylbiguanidinium=n-butyltriphenylborate, (Z)-{[bis(dimethylamino)methylidene]amino}-N-cyclohexyl(cyclohexylamino)methaniminium=tetrakis(3-fluorophenyl)borate, 1,2-diisopropyl-3-[bis(dimethylamino)methylene]guanidinium=2-(3-benzoylphenyl)propionate, N,N-diethylcarbamate 9-anthrylmethyl, (E)-1-piperidino-3-(2-hydroxyphenyl)-2-propen-1-one, imidazole-1-carboxylic acid 1-carboxylate, and the like. -(anthraquinone-2-yl)ethyl, 4-(methacryloyloxy)piperidine-1-carboxylate (2-nitrophenyl)methyl, cyclohexylcarbamate 1,2-bis(4-methoxyphenyl)-2-oxoethyl, cyclohexylcarbamate 2-nitrobenzyl, 2-(9-oxoxoxanthen-2-yl)propionic acid 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 2-(9-oxoxoxanthen-2-yl)propionic acid 1,5-diazabicyclo[4.3.0]non-5-ene, 2-(9-oxoxoxanthen-2-yl)propionic acid 1,8-diazabicyclo[5.4.0]undec-7-ene, acetophenone O-benzoyloxime, 2-(piperidine-1-carbonyl)benzaldehyde, nifedipine, and the like.
[0045] Photoradical polymerization initiator The film-hardening component may contain a photoradical polymerization initiator. The photoradical polymerization initiator is configured to generate radicals when the coating agent is irradiated with ultraviolet light. By blending the photoradical polymerization initiator in the coating agent, radical polymerization of the film-forming component can be advanced, and an organic component can be formed in the coating film.
[0046] Examples of the photoradical polymerization initiator that can be used include acetophenone-based compounds, benzophenone-based compounds, α-ketoester-based compounds, phosphine oxide-based compounds, benzoin compounds, titanocene-based compounds, acetophenone / benzophenone hybrid-based photoinitiators, oxime ester-based photoinitiators, and camphorquinone.
[0047] Examples of acetophenone compounds include 2,2-dimethoxy-1,2-diphenylethan-1-one, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one, diethoxyacetophenone, oligo{2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propanone} and 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)benzyl]phenyl}-2-methylpropan-1-one.
[0048] Examples of the benzophenone compounds include benzophenone, 4-phenylbenzophenone, 2,4,6-trimethylbenzophenone, and 4-benzoyl-4'-methyldiphenyl sulfide, etc. Examples of the α-ketoester compounds include methylbenzoyl formate, 2-(2-oxo-2-phenylacetoxyethoxy)ethyl ester of oxyphenylacetic acid, and 2-(2-hydroxyethoxy)ethyl ester of oxyphenylacetic acid, etc.
[0049] Examples of phosphine oxide compounds include 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide. Examples of benzoin compounds include benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether. Examples of acetophenone / benzophenone hybrid photoinitiators include 1-[4-(4-benzoylphenylsulfanyl)phenyl]-2-methyl-2-(4-methylphenylsulfinyl)propan-1-one. Examples of oxime ester photopolymerization initiators include 2-(O-benzoyloxime)-1-[4-(phenylthio)]-1,2-octanedione.
[0050] As the photoradical polymerization initiator, one compound selected from these compounds may be used, or two or more compounds may be used in combination.
[0051] The content of the film-hardening component in the coating agent and the ratio of the photobase generator to the photoradical polymerization initiator may be appropriately set according to the composition of the film-hardening component, etc. For example, the content of the film-hardening component in the coating agent may be appropriately set within the range of 0.1 parts by mass or more and 10 parts by mass or less per 100 parts by mass of the film-forming component.
[0052] [Other additives] In addition to the film-forming component and the film-hardening component, the coating agent may contain additives known for coating agents within a range that does not impair the hardening of the coating agent.For example, the coating agent may contain additives for suppressing deterioration of the coating film, such as ultraviolet absorbers, radical scavengers, and hindered amine-based light stabilizers.By using these additives, it is expected to improve the weather resistance of the coating film.
[0053] The coating agent may contain, as an additive, a surface conditioner such as a leveling agent or a defoaming agent. By using these additives, the thickness of the coating agent can be made uniform when the coating agent is applied to a substrate. As a result, it is expected that the durability of the resin member provided with the coating film against scratches can be further improved.
[0054] (base material) The substrate used to prepare the resin member is made of a thermoplastic resin. The thermoplastic resin constituting the substrate can be appropriately selected according to the application of the resin member. For example, when the resin member is used as a transparent member for a window, polycarbonate can be used as the substrate. Polycarbonate has excellent properties required for a transparent member for a window, such as weather resistance, strength, and transparency. Therefore, by forming the transparent coating film on a substrate made of polycarbonate, a resin member suitable as a transparent member for a window can be obtained.
[0055] The shape of the substrate is not particularly limited, but from the viewpoint of easier pressing after forming a coating film on the substrate, the substrate preferably has a flat plate shape.
[0056] (Method of manufacturing resin member) In the manufacturing method, first, a coating agent is applied onto the surface of a substrate. The method of applying the coating agent to the substrate is not particularly limited, and an appropriate method may be selected from known application methods according to the desired film thickness, etc. For example, known application devices such as a spray coater, a flow coater, a spin coater, a dip coater, a bar coater, an inkjet coater, and an applicator may be used to apply the coating agent to the substrate.
[0057] After the coating agent is applied to the surface of the substrate, a step of heating and drying the coating agent may be carried out as necessary.
[0058] After applying the coating agent to the surface of the substrate, the coating agent is irradiated with ultraviolet light to harden the coating agent. As described above, when the coating agent is irradiated with ultraviolet light, bases and radicals are generated from the film hardening component. Then, the bases and radicals generated from the film hardening component cause the sol-gel reaction and radical polymerization to proceed in parallel, and a coating film made of a hardened product of the coating agent can be formed on the substrate.
[0059] For the irradiation of ultraviolet light, an appropriate light source can be selected from known light sources capable of generating ultraviolet light, such as a mercury lamp, a metal halide lamp, a light-emitting diode, an excimer lamp, etc., depending on the absorption wavelength of the film curing component, the required light amount, etc. In the curing step, ultraviolet light may be irradiated in an air atmosphere or in a nitrogen atmosphere.
[0060] In the above-mentioned manufacturing method, after forming a coating film on a substrate, a laminate of the substrate and the coating film is heated and pressed. In this manner, by heating the laminate and pressing while the substrate is softened, the substrate is deformed to obtain a resin part having a desired shape.
[0061] In addition, the coating film hardened by irradiation with ultraviolet light contains unreacted hydroxyl groups, alkoxy groups, and (meth)acryloyl groups. Therefore, when heat is applied during pressing, the unreacted hydroxyl groups, alkoxy groups, and (meth)acryloyl groups react, further promoting the hardening of the coating film. As a result, the durability of the coating film against scratches can be further improved.
[0062] The order of heating and pressing the laminate is not particularly limited as long as pressing can be performed while the substrate is softened. For example, the laminate may be heated to a desired temperature to soften the substrate, and then heating is terminated, and pressing is performed while the substrate is softened, thereby forming the laminate into a desired shape. In addition, for example, the laminate may be heated and pressed simultaneously, thereby forming the laminate into a desired shape while softening the substrate.
[0063] The heating temperature when pressing the laminate may be appropriately set according to the type of thermoplastic resin constituting the substrate. From the viewpoint of more reliably softening the substrate, it is preferable to press the laminate while the temperature of the substrate is (Tg-15°C) or more and (Tg+65°C) or less, when the glass transition temperature of the thermoplastic resin constituting the substrate is expressed as Tg. For example, when polycarbonate having a glass transition temperature of 145°C is used as the substrate, it is preferable to press the laminate while the temperature of the substrate is 130°C or more and 210°C or less, and it is more preferable to press the laminate while the temperature of the substrate is 140°C or more and 180°C or less. In this case, the laminate can be softened and the hardening of the coating film can be promoted while avoiding deterioration of the coating film due to heating. EXAMPLES
[0064] (Example) An embodiment of the method for producing the resin member will be described with reference to Fig. 1. As shown in Fig. 1, the resin member 1 of this embodiment has a substrate 2 made of polycarbonate as a thermoplastic resin, and a coating film 3 formed on one side of the substrate 2. The resin member 1 has a substantially rectangular plate shape, and a central portion 11 in the longitudinal direction is gently curved so as to protrude toward the side having the coating film 3 in the thickness direction more than both end portions 12.
[0065] In producing the resin member 1 of this example, first, a substrate 2 and a coating agent for forming a coating film 3 are prepared. Before being pressed, the substrate 2 is a rectangular flat plate made of polycarbonate, as shown in Fig. 2. The coating agent contains a film-forming component including silsesquioxane and (meth)acrylate (excluding the silsesquioxane) having a Ta structural unit represented by the following composition formula (1) and a Tc structural unit represented by the following composition formula (2), and a film-curing component configured to generate a base and a radical when irradiated with ultraviolet light. (R 1 SiO 3 / 2) ···(1) (R 2 SiO 3 / 2 ) ···(2)
[0066] However, R in the composition formula (1) 1 is an acryloyl group or a methacryloyl group, and R in the composition formula (2) 2 is a monovalent hydrocarbon group.
[0067] Next, a coating agent is applied to one side of the substrate 2, and then the coating agent is cured by irradiating it with ultraviolet light. This results in a flat laminate 10 (see FIG. 3) having the substrate 2 and the coating film 3 formed on one side of the substrate 2.
[0068] Thereafter, the laminate 10 is heated and pressed to deform the laminate 10 into a desired shape. For example, in this example, the laminate 10 is first heated so that the temperature of the substrate is equal to or higher than (glass transition temperature of thermoplastic resin Tg-15°C) and equal to or lower than (Tg+65°C). Thereafter, while the temperature of the substrate is within the specific range, the laminate 10 is pressed.
[0069] To press the laminate 10, for example, a molding die 4 as shown in FIG. 3 can be used, which includes a first die 41 and a second die 42, with a molding gap 43 having a shape corresponding to the resin member 1 shown in FIG. 1 between the first die 41 and the second die 42.
[0070] Alternatively, instead of the above-mentioned method, the heating and pressing of the laminate 10 can be performed simultaneously. In this case, for example, the laminate 10 may be pressed in a state in which the temperature of the molding die 4 shown in Fig. 3 is increased. In either case, by pressing the laminate 10 while the base material 2 is softened, the laminate 10 can be molded into a shape corresponding to the molding gap 43, and the resin member 1 shown in Fig. 1 can be obtained.
[0071] In the manufacturing method of the resin member of this example, a coating agent containing the specific silsesquioxane and (meth)acrylate is applied onto a substrate, and then ultraviolet light is irradiated. When the coating agent is irradiated with ultraviolet light, a base and radicals are generated from the film-curing component. The base generated from the film-curing component can condense the silsesquioxane through a sol-gel reaction. In addition, the radicals generated from the film-curing component can polymerize the (meth)acrylate and the silsesquioxane through radical polymerization.
[0072] Therefore, by irradiating the coating agent with ultraviolet light, the sol-gel reaction and the radical polymerization can proceed in parallel, resulting in segregation of inorganic components derived from silsesquioxane on the surface of the coating film, improving the durability against scratches, and segregation of organic components in the coating film near the substrate, improving adhesion to the substrate.
[0073] In addition, the coating film made of the cured product of the coating agent has relatively high toughness. Therefore, when a laminate of a substrate and the coating film is pressed while being heated, the coating film easily deforms in accordance with the deformation of the substrate. As a result, a resin part having a desired shape can be obtained while suppressing the occurrence of cracks in the coating film. Furthermore, by heating the coating film together with the substrate, the hydroxyl groups, alkoxy groups, and (meth)acryloyl groups present in the coating film can be reacted. As a result, the coating film can be sufficiently cured, and the durability of the coating film against scratches can be further improved.
[0074] Therefore, according to the manufacturing method of this example, a coating film that has excellent adhesion to the substrate and durability against scratches can be formed by simple operations, and a resin member can be obtained that can suppress the occurrence of cracks in the coating film when the substrate is deformed by pressing.
[0075] (Experimental Example) In this example, a resin member was prepared using coating agent A1 having the composition shown in Table 1, and its weather resistance and durability against scratches were evaluated.
[0076] [Table 1]
[0077] The silsesquioxane, (meth)acrylate, and film-curing component used in the preparation of the coating agent of this example are specifically as follows.
[0078] [Film forming component] Silsesquioxane B1 Methyltrimethoxysilane and methacryloxypropyltriethoxysilane were mixed in a molar ratio of methyltrimethoxysilane:methacryloxypropyltriethoxysilane=5:5, and the mixture was condensed by a known method to obtain silsesquioxane B1 shown in Table 1. The weight average molecular weight of silsesquioxane B1 was 6,500. The weight average molecular weight of silsesquioxane B1 is a polystyrene-equivalent value obtained by gel permeation chromatography.
[0079] (Meth)acrylate C1 The (meth)acrylate C1 is a mixture containing an isocyanuric acid ethylene oxide modified triacrylate (specifically, "M-315" manufactured by Toagosei Co., Ltd.). (Meth)acrylate C2 (Meth)acrylate C2 is specifically methyl 2-(allyloxymethyl)acrylate.
[0080] [Film curing component] Photobase generator D1 The photobase generator D1 is specifically 1,2-diisopropyl-3-[bis(dimethylamino)methylene]guanidium=2-(3-benzoylphenyl)propionate. Photoradical polymerization initiator E1 The photoradical polymerization initiator E1 is bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (specifically, "Omnirad (registered trademark) 819" manufactured by IGM Resins BV). Photoradical polymerization initiator E2 The photoradical polymerization initiator E2 is a mixture of 2-(2-oxo-2-phenylacetoxyethoxy)ethyl ester of oxyphenylacetic acid and 2-(2-hydroxyethoxy)ethyl ester of oxyphenylacetic acid (specifically, "Omnirad754" manufactured by IGM Resins BV).
[0081] In this example, the above-mentioned compounds were dissolved in a solvent in the ratio shown in Table 1 to prepare coating agent A1.
[0082] Next, a 5 mm thick polycarbonate substrate was prepared, and the surface of the substrate was coated with Coating Agent A1 using a bar coater. After Coating Agent A1 was coated on the substrate, the substrate was pre-baked by heating it for 3 minutes in a hot air drying oven set at 100°C.
[0083] After pre-baking, the coating agent A1 was irradiated with ultraviolet light to form a coating film made of a cured product of the coating agent A1 on the substrate. In this example, the ultraviolet light was irradiated in a nitrogen atmosphere. A high-pressure mercury lamp was used as the source of the ultraviolet light. The illuminance of the ultraviolet light was 250 mW / cm. 2 The exposure dose was 2500 mJ / cm 2 It was decided.
[0084] After irradiation with ultraviolet light, the laminate of the substrate and the coating film was heated using a heating furnace set at a temperature of 160°C to soften the substrate. The laminate was then pressed while the temperature of the substrate was 140°C or higher to obtain a test material S1 shown in Table 2. The shape of the test material S1 was a flat plate. The thickness of the coating film formed on the substrate was about 20 μm.
[0085] In this example, for comparison with test material S1, test material R1 shown in Table 2 was prepared. The method for preparing test material R1 was the same as that for preparing test material S1, except that the laminate was not heated or pressed after the coating film was formed on the substrate by irradiating it with ultraviolet light.
[0086] The methods for evaluating the weather resistance and durability against scratches of the test materials S1 and R1 are as follows.
[0087] [Durability against scratches] A Taber abrasion test was performed on the coating film, and the durability against scratches was evaluated based on the increase in haze value ΔH (unit: %) after the abrasion test. More specifically, the haze value of the test material before the abrasion test was measured, and then the test material was attached to the Taber abrasion tester. The abrasion test was performed by rotating the abrasion wheel to abrade the coating film of the test material. The abrasion wheel of the Taber abrasion tester in this example is CS-10F. The load in the abrasion test is 500 gf, and the number of rotations is 1000.
[0088] After the abrasion test was performed under the above conditions, the haze value of the test material after the test was measured using a haze meter. The increase in haze value was calculated by subtracting the haze value of the test material before the test from the haze value of the test material after the test. The increase in haze value ΔH (unit: %) for each test material is shown in the "Durability against scratches" column in Table 2.
[0089] ·Weather resistance Accelerated weather resistance tests were carried out using an ultra-accelerated weather resistance tester ("Metal Weather (registered trademark)" manufactured by Daipla Wintes Co., Ltd.). In the accelerated weather resistance tests, one cycle consisted of a step of irradiating the test material with ultraviolet light generated from a metal halide lamp and a step of pausing irradiation and allowing the test material to condense, and this cycle was repeated.
[0090] The method for evaluating the presence or absence of peeling of the coating film is as follows. First, in the accelerated weather resistance test, the test material was taken out of the test machine after condensation. After drying the test material, a transparent pressure-sensitive adhesive tape was attached to the coating film. The width of the tape was 25 mm, and the adhesive strength of the tape per 25 mm width, measured according to IEC 60454-2, was 10±1 N / 25 mm. The tape was then peeled off at a roughly constant speed. Then, the presence or absence of peeling of the coating film in the area where the tape was attached was visually confirmed. In addition, the presence or absence of cracks in the coating film was visually evaluated. For each test material, the number of cycles (unit: times) when peeling of the coating film from the substrate occurred and the number of cycles (unit: times) when cracks occurred were as shown in Table 2.
[0091] [Table 2]
[0092] As shown in Table 2, test material S1, in which the laminate was heated and pressed, was able to suppress peeling and cracking of the coating film in the accelerated weather resistance test, compared to test material R1, in which neither heating nor pressing was performed. Furthermore, test material S1 had a smaller increase in haze value after the abrasion test than test material R1, and was superior in durability against scratches.
[0093] Therefore, from these results, it can be understood that by heating and pressing the laminate after irradiation with ultraviolet light, it is possible to improve the adhesion between the coating film and the substrate and the resistance to scratches.
[0094] The above describes the aspects of the method for manufacturing the resin member based on the embodiments and experimental examples. However, the specific aspects of the method for manufacturing the resin member according to the present invention are not limited to the embodiments and experimental examples, and the configuration can be appropriately changed within the scope that does not deviate from the spirit of the present invention.
[0095] For example, in the embodiment, an example in which the coating film 3 is formed on one side of the substrate 2 is shown, but the coating film 3 can also be formed on both sides of the substrate 2 .
[0096] For example, the method for producing a resin member may take the following aspects (1) to (6).
[0097] [1] A coating agent is applied onto a substrate made of a thermoplastic resin, the coating agent including a film-forming component including a silsesquioxane having a Ta structural unit represented by the following composition formula (1) and a Tc structural unit represented by the following composition formula (2) and a (meth)acrylate (excluding the silsesquioxane), and a film-curing component configured to generate a base and a radical when irradiated with ultraviolet light, Thereafter, the coating agent is irradiated with ultraviolet light to form a coating film made of a cured product of the coating agent on the substrate; Thereafter, the laminate of the substrate and the coating film is heated and pressed to obtain a resin member having a desired shape. (R 1 SiO 3 / 2 ) ···(1) (R 2 SiO 3 / 2 ) ···(2) (However, R in the composition formula (1) 1 is an acryloyl group or a methacryloyl group, and R in the composition formula (2) 2 is a monovalent hydrocarbon group.
[0098] [2] The method for producing a resin member according to [1], wherein the laminate is pressed while the temperature of the base material is equal to or higher than (the glass transition temperature of the thermoplastic resin, Tg-15°C) and equal to or lower than (Tg+65°C). [3] The method for producing a resin member according to [1] or [2], wherein the silsesquioxane further contains a Q structural unit represented by the following composition formula (3): (SiO 4 / 2 ) ···(3)
[0099] [4] The method for producing a resin member according to any one of [1] to [3], wherein the content of the silsesquioxane is 30 parts by mass or more and 150 parts by mass or less per 100 parts by mass of the (meth)acrylate. [5] The method for producing a resin member according to any one of [1] to [4], wherein the film-curing component contains a photobase generator configured to be capable of generating a base when irradiated with ultraviolet light, and a photoradical polymerization initiator configured to be capable of generating radicals when irradiated with ultraviolet light. [6] The method for producing a resin member according to any one of [1] to [5], wherein the (meth)acrylate has an isocyanuric ring. [Explanation of symbols]
[0100] 1 Resin material 2 Base material 3. Coating film
Claims
1. A coating agent is applied onto a substrate made of a thermoplastic resin, the coating agent including a film-forming component including a silsesquioxane having a Ta structural unit represented by the following composition formula (1) and a Tc structural unit represented by the following composition formula (2) and a (meth)acrylate (excluding the silsesquioxane), and a film-curing component configured to generate a base and a radical when irradiated with ultraviolet light, Thereafter, the coating agent is irradiated with ultraviolet light to form a coating film made of a cured product of the coating agent on the substrate; Thereafter, the laminate of the substrate and the coating film is heated and pressed to obtain a resin member having a desired shape. (R 1 SiO 3 / 2 ) ・・・(1) (R 2 SiO 3 / 2 ) ・・・(2) (However, R in the composition formula (1) 1 is an acryloyl group or a methacryloyl group, and R in the composition formula (2) 2 is a monovalent hydrocarbon group.
2. 2. The method for producing a resin member according to claim 1, wherein the laminate is pressed while the temperature of the base material is equal to or higher than (a glass transition temperature (Tg) of the thermoplastic resin - 15°C) and equal to or lower than (Tg + 65°C).
3. The method for producing a resin member according to claim 1 or 2, wherein the silsesquioxane further contains a Q structural unit represented by the following composition formula (3): (No) 4 / 2 ) ・・・(3)
4. The method for producing a resin member according to claim 1 or 2, wherein a content of the silsesquioxane is 30 parts by mass or more and 150 parts by mass or less with respect to 100 parts by mass of the (meth)acrylate.
5. 3. The method for producing a resin member according to claim 1, wherein the film curing component contains a photobase generator configured to be capable of generating a base when irradiated with ultraviolet light, and a photoradical polymerization initiator configured to be capable of generating radicals when irradiated with ultraviolet light.
6. The method for producing a resin member according to claim 1 or 2, wherein the (meth)acrylate has an isocyanuric ring.
Citation Information
Patent Citations
Coated member
JP2006240294A